Incumbency and Entry in License Auctions: The Anglo-Dutch Auction Meets Other Simple Alternatives - Helmuts Azacis; Roberto Burguet (Cardiff University, Cardiff Business School, 2005)
The existence of ex-ante strong incumbents may constitute a barrier to entry in auctions for goods such as licenses. Introducing inefficiencies that favor entrants is a way to induce entry and thus create competition. Designs such as the Anglo-Dutch auction have been proposed with this goal in mind. We first show that indeed the Anglo- Dutch auction fosters entry and increases the revenues of the seller. However, we argue that a more eective way could be to stage the allocation of the good so that each stage reveals information about the participants. We show that a sequence of English auctions, with high reserve prices in early rounds, is a procedure with this property that is more efficient than any one-stage entry auction. Moreover, it also dominates the Anglo-Dutch auction in terms of seller's revenues.
Keywords: 330